The Effect of Liquidity, Leverage, and Working Capital Turn on Profitability - Hidayat, Imam; Dewi, Filla Oktapia Sulistia (Pandawan, 2023)
The purpose of this research is to analyze the effect of liquidity, leverage, and working capital turnover on profitability in coal mining companies listed on the Indonesia Stock Exchange from 2017 to 2020. The data used in this study is quantitative. The data used is secondary data. The Sampling technique used is purposive sampling, and there were 12 firms with research for four years; this obtained 48 observations. The data analysis method used in this study is Panel data regression analysis using reviews 9. The F test result is an F-statistic of 143.6753 > F Table (2.82) and a Prob (F-statistic) value of 0.000000 < 0.05, which means liquidity, leverage, and working capital turnover have a significant effect on profitability. The results of the liquidity t-test are a t statistic (1.198727) < t table (2.01537) and the value of Prob. 0.2371 > 0.05 means that liquidity has no significant effect on profitability. The results of the t-test leverage t statistic (20.47374) > t table (2.01537) and the value of Prob. 0.0000 > 0.05 means that leverage has a significant effect on profitability. The results of the t-test of working capital turnover t statistic (0.986827) < t table (2.01537) and the value of Prob. 0.3291> 0.05 means that working capital turnover has no significant effect on the profitability of coal mining sub-sector companies listed on the Indonesia Stock Exchange.